Electrospun Polycaprolactone (PCL)-Amnion Nanofibrous Membrane Promotes Nerve Regeneration and Prevents Fibrosis in a Rat Sciatic Nerve Transection Model - Bai, Jiangbo; Liu, Chunjie; Kong, Lingde; Tian, Siyu; Yu, Kunlun; Tian, Dehu (Frontiers in Surgery, 2022)
Functional recovery after peripheral nerve injury repair is typically unsatisfactory. An anastomotically poor microenvironment and scarring at the repair site are important factors impeding nerve regeneration. In this study, an electrospun poly-e-caprolactone (PCL)-amnion nanofibrous membrane comprising an amnion membrane and nonwoven electrospun PCL was used to wrap the sciatic nerve repair site in the rat model of a sciatic nerve transection. The effect of the PCL-amnion nanofibrous membrane on improving nerve regeneration and preventing scarring at the repair site was evaluated by expression of the inflammatory cytokine, sciatic functional index (SFI), electrophysiology, and histological analyses. Four weeks after repair, the degree of nerve adhesion, collagen deposition, and intraneural macrophage invasion of the PCL-amnion nanofibrous membrane group were significantly decreased compared with those of the Control group. Moreover, the PCL-amnion nanofibrous membrane decreased the expression of pro-inflammatory cytokines such as interleukin(IL)-6, Tumor Necrosis Factor(TNF)-a and the number of pro-inflammatory M1 macrophages, and increased the expression of anti-inflammatory cytokine such as IL-10, IL-13 and anti-inflammatory M2 macrophages. At 16 weeks, the PCL-amnion nanofibrous membrane improved functional recovery, including promoting nerve Schwann cell proliferation, axon regeneration, and reducing the time of muscle denervation. In summary, the PCL-amnion nanofibrous membrane effectively improved nerve regeneration and prevent fibrosis after nerve repair, which has good clinical application prospect for tissue repair.